Impacts of long-term different fertilization regimes on microbial utilization of straw-derived carbon in greenhouse vegetable soils: insights from its ecophysiological roles and temperature responses - Ma, Long; Li, Ruonan; Luan, Haoan; Tang, Jiwei; Wang, Liying; Guo, Tengfei; Huang, Shaowen (Frontiers in Plant Science, 2024)
As the largest organic carbon input in the agroecosystems, crop residues can increase soil carbon sequestration and crop production in greenhouse vegetable fields (GVFs). However, the soil microbiological mechanisms driving straw decomposition in GVFs under different incubation temperatures and fertilization treatments are not clear. Thus, soil samples were collected from a long-term field experiment included chemical fertilizer application alone (CF), 2/4 fertilizer N+2/4 organic fertilizer N (CM), 2/4 fertilizer N+1/4 organic fertilizer N+1/4 straw N (CMS), 2/4 fertilizer N+2/4 straw N (CS), and incubated with 13 C-labeled straw at different temperatures (15, 25, and 35 ℃) for 60 days. Organic-amended treatments (CM, CMS, and CS), especially CMS treatment, increased soil bacterial Alpha diversity before and after straw addition. Straw decomposition process was dominated by soil Proteobacteria, Actinobacteria, and Firmicutes for each treatments. The effect of incubation temperature on soil microbial community composition was higher than that of fertilization treatments. Soil Alphaproteobacteria and Actinomycetia were the most predominant class involved in straw decomposition. Gammaproteobacteria (Pseudomonas, Steroidobacter, Acidibacter, and Arenimonas) were the unique and predominant class involved in straw decomposition at medium and high temperatures as well as in the straw-amended treatments. Organic-amended treatments, especially straw-amended treatments, increased the relative abundance of glycosyl transferases (GT) and auxiliary activities (AA). Alphaproteobacteria, Actinomycetia, and Gammaproteobacteria had higher relative contribution to carbohydrase genes. In summary, the long-term organic-amended treatments altered the structure of soil microbial communities and increased soil bacterial diversity, with the CMS having a greater potential to enhance resistance to external environmental changes. Soil Alphaproteobacteria and Actinomycetia were responsible for the dominance of straw decomposition, and Gammaproteobacteria may be responsible for the acceleration of straw decomposition. Fertilization treatments promote straw decomposition by increasing the abundance of indicator bacterial groups involved in straw decomposition, which is important for isolating key microbial species involved in straw decomposition under global warming.